2008
DOI: 10.21273/horttech.18.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Kaolin Particle Film Product Applications Before Harvest Begins May Not Improve Marketable Yields of Fresh Tomatoes

Abstract: Drip-irrigated, stake-and-weave supported tomato (Lycopersicon esculentum) plots were established in 2005 and 2006. All plots (except controls) were treated with a kaolin particle film product (Surround WP) mixed at 0.5 lb/gal of water and applied with a pressurized hand sprayer. Sprays began after transplanting and were repeated as needed to maintain a particle film on the foliage. Sprays were discontinued either at anthesis, at first green fruit 5 cm in diameter, or at firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Tests indicate a higher leaf carbon assimilation rate and a reduced canopy temperature in grapefruit and apples . That explains why this product is labelled for reduction of heat stress and sunburn on several crops . Kaolin cools tissues and protects plants from extreme heat and ultraviolet radiation by increasing leaf reflectance and reducing transpiration rate .…”
Section: Zeolites: a Good Particle Film For Controlling Pests And Dismentioning
confidence: 99%
See 3 more Smart Citations
“…Tests indicate a higher leaf carbon assimilation rate and a reduced canopy temperature in grapefruit and apples . That explains why this product is labelled for reduction of heat stress and sunburn on several crops . Kaolin cools tissues and protects plants from extreme heat and ultraviolet radiation by increasing leaf reflectance and reducing transpiration rate .…”
Section: Zeolites: a Good Particle Film For Controlling Pests And Dismentioning
confidence: 99%
“…24,65,67 That explains why this product is labelled for reduction of heat stress and sunburn on several crops. 4 Kaolin cools tissues and protects plants from extreme heat and ultraviolet radiation by increasing leaf reflectance and reducing transpiration rate. 68 Experiments with kaolin demonstrated that leaf temperature increases linearly with increasing light intensity.…”
Section: Effects Of Zeolites On the Plantmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, Abd El-Aal et al (2008) mentioned that foliar application of MgCO3 at rate 2% gained more growth vigor and more fruits yield as well as better physical and chemical properties of eggplant compared with no-treated plants. Kaolin also is an important material used in this concern, it is considered as an effective natural antitranspirant and was reported to mitigate the negative effects of water deficiency and environmental stresses, such as heat stress and sunburn damage as well as suppress diseases and protect crops from insect pests (Kahn and Damicone, 2008). Spraying tomato plants with 5% of kaolin suspension improved water status and yield under water stress conditions (Srinivasa Rao, 1985).…”
Section: Introductionmentioning
confidence: 99%